“BEING ON GUARD” VS “BEING IN BLINKERS”: PERSPECTIVES ON THE INTERCULTURAL COMPETENCE WITH FOREIGN MEDICAL STUDENTS IN ROMANIA. ASPECTS OF EVALUATION - URSA, Anca (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Being on guard vs being in blinkers: perspectives on the intercultural competence with foreign medical students in Romania. Aspects of evaluation. The development of intercultural competence (IC) in the 21st century is a clear necessity, and not a socio-political trend. If in the United States circumstances have imposed for decades the establishment of a new discipline, Europe sees itself now confronted with the emergency of establishing intercultural teaching principles, in the face of massive immigration and an explosion in educational and occupational mobility. If we relate to the second category, foreign medical students in Romania respond to a double wager of understanding Romanians: the street and the hospital medium. From a pedagogical perspective, the work group is homogeneous, so that teaching transcultural knowledge, attitudes and abilities does not raise major problems. However, evaluation represents a challenge: it is not a question of knowledge, where there already are multiple instruments that have been verified, but about attitudes and abilities, which are monitored in time and in specific contexts, and the RFL teacher rarely benefits from such circumstances. In the present study, „ Being on Guard Vs Being in Blinkers: Perspectives on the Intercultural Competence with Foreign Medical Students in Romania. Aspects Of Evaluation”, we try to build some evaluation activities and exercises that are specific for each component of the intercultural competence, and which are adapted to the students’ curriculum and schedule. Rezumat. Cu ochii în patru vs. cu ochelari de cal: perspective asupra competenței interculturale la studenții mediciniști străini din România. Aspecte ale evaluării. Dezvoltarea competenței interculturale în secolul XXI este o necesitate clară, nu un trend sociopolitic. Dacă în Statele Unite circumstanțele au impus de câteva decenii deja constituirea noii discipline, Europa se vede acum confruntată cu urgența constituirii principiilor didactice interculturale, în fața imigrației masive și a exploziei mobilităților educaționale. Dacă ne raportăm la a doua categorie, studenții străini mediciniști din România răspund unui dublu pariu al înțelegerii românilor: strada și mediul spitalicesc. Din perspectivă pedagogică, grupul de lucru e omogen, deci predarea cunoștințelor, atitudinilor și abilităților transculturale nu ridică probleme majore. Însă evaluarea e o provocare: nu e vorba de cunoștințe, unde deja există intrumente multiple și verificate, ci de atitudini și abilități, care se monitorizează în timp și în contexte specifice, iar profesorul de RLS dispune rareori de asemenea circumstanțe. În studiul de față încercăm să construim câteva activități și exerciții de evaluare specifice pentru fiecare componentă a competenței interculturale, adaptate la curriculumul și orarul studenților noștri. Cuvinte cheie: competență interculturală, metode de evaluare, atitudini, abilități, activități integrate.